Perbandingan Acute Physiology dan Chronic Health Evaluation II (APACHE II) dan Sequential Organ Failure Assessment (SOFA) Sebagai Prediktor Mortalitas Pasien COVID - 19 - Bima Permana; Amadea Hasian (Majalah Anestesia & Critical Care, 2022)
COVID-19 pandemic has caused massive impact on healthcare facility around the world. Variable clinical spectrum and prognosis made it difficult to predict patients’ mortality. This writing is aimed to compare two most used tool for critically ill patients, Acute Physiology and Chronic Health Evaluation II (APACHE II) and Sequential Organ Failure Assessment (SOFA) as mortality predictor for COVID-19 patients. APACHE-II performed better in predicting mortality and prognosis in COVID-19 compared to SOFA due to broad comorbidities evaluation. Age and comorbidities are two important roles in severity and death in COVID-19. Thus, APACHE-II might be useful for further clinical decisions and therapies.